Relationship between postoperative retear and preoperative fatty degeneration in large and massive rotator cuff tears: quantitative analysis using T2 mapping - Iijima, Yuki; Matsuki, Keisuke; Hoshika, Shota; Ueda, Yusuke; Hamada, Hiroshige; Tokai, Morihito; Takahashi, Norimasa; Sugaya, Hiroyuki; Watanabe, Atsuya (Journal of shoulder and elbow surgery, 2019)
Fatty degeneration of the rotator cuff muscles is reported to be associated with retear after rotator cuff repair. The purpose of this study was to assess the relationship between retear and preoperative fatty degeneration, as quantified by T2 mapping. This prospective cohort study included 83 large and 24 massive rotator cuff tears (average age, 67 years; range, 46-82 years). All patients preoperatively underwent T2 mapping magnetic resonance imaging, and T2 values of the supraspinatus and infraspinatus muscles were quantified. Cuff integrity was evaluated with magnetic resonance imaging 1 year postoperatively. Preoperative T2 values were compared between the retear and intact groups. The preoperative Goutallier stage, Constant score, and the shoulder score of the University of California at Los Angeles were also compared between the 2 groups. Retear was found in 32 shoulders (30%). Postoperative Constant and University of California at Los Angeles scores were significantly higher in intact shoulders than in retear shoulders (P < .001 for both). Mean preoperative T2 values of supraspinatus and infraspinatus were 77.4 ± 13.2 ms and 73.2 ± 15.3 ms in retear shoulders and 66.5 ± 11.1 ms and 58.6 ± 11.7 ms in intact shoulders, respectively; the differences were significant in both muscles (P < .001). Cutoff values for prediction of retear were 71.8 ms in supraspinatus and 63.1 ms in infraspinatus. There were no significant differences in the preoperative Goutallier stages of supraspinatus and infraspinatus between the 2 groups. Retear shoulders demonstrated significantly higher preoperative T2 values than intact shoulders. T2 mapping can be a useful tool for predicting postoperative retears.